Pesantren and Tarekat in the Modern Era: An Account of the Transmission of Traditional Islam in Java - Muhaimin AG. (Studia Islamika, 1997)
In Java, boarding schools and institutes are the two institutions that usually bears the stamp of Traditional Islam. Both institutions have the same mission, namely conveying and preserving the Islamic tradition from generation to generation. More specialized mission boarding schools in the transmission of Islamic tradition among the younger generation so that they are ready to take active roles in society without forgetting the long-term goals, which is looking for safety and happiness in the life hereafter. While the congregation Islamic tradition prefers transmission among hosts that they are prepared for life in the hereafter at the time was the end of life draws near. Often also occurs in both the mission there, or assumed by, the same institution. Pesantren Buntet is one example of the vitality and dynamics in the mission is interesting to watch.DOI: 10.15408/sdi.v4i1.785